Correlation of Ischemia-Modified Albumin with SOFA and APACHE II Scores in Preoperative Patients with Colorectal Cancer - Masaaki Satoh; Kazuhiko Kotani; Alejandro Gugliucci; Hisanaga Horie; Russell Caccavello; Mamoru Takeuchi (The Scientific World Journal)
Purpose. Critical illnesses are assessed according to the sequential organ failure assessment (SOFA) and acute physiology and chronic health evaluation (APACHE) II. Circulating ischemia-modified albumin (IMA) is a biomarker generated under ischemic and oxidative conditions and may reflect disease severity in preoperative patients. This study investigated the correlations of IMA with SOFA and APACHE II scores in inpatients admitted for colorectal surgery. Methods. We examined 27 patients with advanced colorectal cancers (mean age 69 years, men/women = 15/12). Correlations between SOFA and APACHE II scores in addition to preoperative serum IMA and C-reactive protein (CRP) levels were analyzed. Results. The mean IMA level was 0.5 AU, and the median CRP level was 0.6 mg/dL. Median scores for SOFA and APACHE II were 2 and 12 points, respectively. Significant positive correlations between IMA and SOFA (r=0.45, P<0.05) and IMA and APACHE II (r=0.45, P<0.05) were identified which remained significant in confounder-adjusted analyses. In contrast, weak correlations were observed between CRP and the SOFA and APACHE II scores. Conclusions. The positive correlations between IMA and both SOFA and APACHE II scores suggest that serum IMA measurements reflect the severity of systemic failure in patients admitted for colorectal surgery in the preoperative phase.